ANALYSIS OF FACTORS INFLUENCING DEBT POLICY IN PHARMACEUTICAL COMPANIES - M. Firza Alpi (CERED Indonesia Institute, 2021)
Debt policy is one of the external funding decisions. Debt policy is the company's policy of using debt funds by maximizing the debt to obtain a high level of return on profits. This study aims to determine the effect of Asset Structure and Profitability on Debt Policy on Pharmaceutical companies listed on the Indonesia Stock Exchange. This research approach uses an associative approach. The population used is 9 companies, the method of determining the number of samples in this study is non-probability sampling and the selected sample as many as 7 companies. The results showed that the Asset Structure partially had no significant effect on Debt Policy, while Profitability had a negative and significant impact on debt policy. Then simultaneously the Asset Structure and Profitability have a significant effect on debt policy on pharmaceutical companies listed on the Indonesia Stock Exchange.